Didactic considerations for the learning process of keyboarding - Solís Chaverri, Brandon (2024)
To operate the computer keyboard by touch quickly and accurately requires constant practice using methodologies and practice materials designed so that students develop typing skills at the highest possible level. The objective of this article is to present didactic considerations that facilitate the learning process. The methodology used in this study was documentary; a bibliographic review was conducted to analyze the information and thus provide teaching methods and guidelines for the development of practice material for learning the skill of speed and accuracy. In this way, the business educator will have a guide that provides input for their planning so that the student population can achieve the established goals.